Understanding Extension for School-Based Agricultural Education #3: FFA and 4-H—A Comparison - Debra Barry; Alyssa J. Shepherd; Jennifer Patton; Stephen Gran (EDIS, 2020)
Even though many recognize FFA and 4-H, there is still a big disconnect in understanding the similarities and differences between them. This 4-page document serves as an educational tool for school-based agricultural education and 4-H programs, and provides a background of the history, characteristics, and membership process of these long-standing organizations. Written by Debra Barry, Alyssa Shepherd, Jennifer Patton, and Stephen Gran, and published by the UF/IFAS Department of Agricultural Education and Communication, September 2020.